Benoxacor is enantioselectively metabolized by rat liver subcellular fractions. (1st October 2020) - Simonsen, Derek; Cwiertny, David M.; Lehmler, Hans-Joachim
Abstract: This study investigated the enantioselective metabolism of benoxacor, an ingredient of herbicide formulations, in microsomes or cytosol prepared from female or male rat livers. Benoxacor was incubated for ≤30 min with microsomes or cytosol, and its enantioselective depletion was measured using gas chromatographic methods. Benoxacor was depleted in incubations with active microsomes in the presence and absence of NADPH, suggesting its metabolism by hepatic cytochrome P450 enzymes (CYPs) and microsomal carboxylesterases (CESs). Benoxacor was depleted in cytosolic incubations in the presence of glutathione, consistent with its metabolism by glutathione S-transferases (GSTs). The depletion of benoxacor was faster in incubations with cytosol from male than female rats, whereas no statistically significant sex differences were observed in microsomal incubations. The consumption of benoxacor was inhibited by the CYP inhibitor 1-aminobenzotriazole, the CES inhibitor benzil, and the GST inhibitor ethacrynic acid. Estimates of the intrinsic clearance of benoxacor suggest that CYPs are the primary metabolic enzyme responsible for benoxacor metabolism in rats. Microsomal incubations showed an enrichment of the first eluting benoxacor enantiomer (E1 -benoxacor). A greater enrichment occurred in incubations with microsomes from female (EF = 0.67 ± 0.01) than male rats (EF = 0.60 ± 0.01). Cytosolic incubations from female rats resulted in enrichment of E1 -benoxacor (EF = 0.54 ± 0.01), while cytosolic incubations from male rats displayed enrichment of the second eluting enantiomer (E2 -benoxacor; EF = 0.43 ± 0.01). Sex-dependent differences in the metabolism of benoxacor in rats could significantly impact ecological risks and mammalian toxicity. Moreover, changes in the enantiomeric enrichment of benoxacor may be a powerful tool for environmental fate and transport studies. Graphical abstract: Image 1 Highlights: Benoxacor is metabolized by rat the hepatic cytochrome P450 system and carboxylesterases in vitro . Benoxacor is metabolized by hepatic glutathione S-transferases in vitro . The in vitro metabolism of benoxacor is sex-dependent in rats. Benoxacor is enantioselectively metabolized by different drug metabolizing enzymes.